Pengaruh Penambahan Ag Terhadap Struktur Kristal dan Sifat Optik Fe3O4, serta Variasi Massa Nanokomposit Fe3O4/Ag terhadap Karakteristik Kurva Surface Plasmon Resonance Menggunakan Metode Sintesis Hijau - Flora Rosdiana Lumbansiantar; Edi Suharyadi; Suprihatin; Posman Manurung (Jurnal Teori dan Aplikasi Fisika, 2026)
Surface plasmon resonance (SPR) phenomenon was observed using the Kretschmann configuration with a four-layer structure: prism/Au Thin Film/ Fe3O4/Ag/air, with Fe3O4/Ag nanocomposite mass variation of 0.025; 0.05; 0.075; and 0.1 gram. Fe3O4 which was then added with 100 mM Ag to become Fe3O4/Ag 100 mM nanocomposite was synthesized using green synthesis method, and then characterized by XRD and UV-Vis. XRD results showed the addition of Ag to Fe3O4 does not change the crystal structure of Fe3O4 directly, but causes an increase in crystallite size. UV-Vis results showed the absorbance spectrum shifted to longer wavelengths. Deposition of Au thin layer on the prism side using vacuum evaporator. Fe3O4/Ag was deposited on the Au thin film using spray method. For the initial configuration of  prism/Au Thin Film/air, the SPR angle (θSPR) of 45.67º was obtain with a minimum reflectance (Rmin) of 0.4208. After the addition of Fe3O4/Ag with each mass, the SPR angle (θSPR) shifted to 45.98º; 46.38º; 46.75º; and 46.77º with a minimum reflectance (Rmin) of 0.5645; 0.6977; 0.7239; and 0.7663. The resulting angular shifts were 0.31º; 0.71º; 1.08º; and 1.11º. The results show that the addition of Fe3O4/Ag to the Au thin layer causes a shift in the SPR angle towards a larger incident angle, as well as increasing the minimum reflectance value. The greater the mass of nanocomposite added, the greater the SPR angle shift that occurs.     Keywords: Fe3O4/Ag nanocomposite, green synthesis, surface plasmon resonance (SPR), UV-Vis, XRD.